Depiction of Diseases in Literature - Akhmedovna, Bakhronova Matluba; Nosirovna, Tolibova Nodira (International Journal of Psychosocial Rehabilitation, 2020)
The widespread use in the language of medicine of words and phrases from commonly used English vocabulary, acquiring a different meaning in the medical context, speaks of the special culture of a special language. Comparison of non-terminological English-Russian correspondences and the features of their use in the language being studied is necessary for specialists in order to communicate effectively. The article discusses the features of the functioning of professional and colloquial medical vocabulary.The results of a study of the functional-style redistribution of medical vocabulary are presented. It is emphasized that each social institution secures for itself a certain symbolic and subject-practical space of activity in which professionals play the leading role. Professionals are distinguished not only by specialized training and qualifications, but also by proficiency in a professional language. Professionalisms are the so- called informal substitutes, colloquial equivalents of terms, legalized, codified names of special concepts of any science.